PKM Karang Taruna Nusa Persada Desa Kalimanggiswetan dalam Mendirikan Taman Baca - Darsih, Endang; Hanggara, Agie; Asikin, Nida Amalia (Empowerment, 2022)
The problem behind this community service is related to the low interest in reading for school-age children and inactive Nusa Persada youth organization in Kalimanggiswetan village. Therefore, the solution offered to solve this problem is by establishing a Taman Baca directly and coaching youth groups in managing the Taman Baca. This Taman Baca was established in Pahing hamlet, precisely at the Village Hall, Kalimanggiswetan. Pahing Hamlet was chosen as Taman Baca location due to a relatively high population of children. In addition, Pahing Hamlet, which is also the Karang Taruna basecamp, has a very strategic location and is easy to reach by the children of the Kalimanggiswetan village. Several series of activities in this service include outreach to community members and schools, exposure and counseling about the importance of Taman Baca by several lecturers, coordination with the Village Government and Youth Organizations in preparing a place for Taman Baca, providing reading materials, equipment and supplies for Taman Baca, carrying out teaching and assistance activities for children that focus on improving literacy both cultural and digital literacy. Regarding the evaluation, the Village Head is also involved to encourage the success of the establishment of Taman Baca and to monitor the success of the program and monitor the sustainability of this Taman Baca.